A glance at the case series and their analysis units - Luis Alberto Corona Martínez; Mercedes Fonseca Hernández (Medisur)
Case series are a particular type of study that is very frequently used in clinical research. This article intends to highlight the usefulness and full validity of these studies as proposals for completion projects of the specialty, as well as to address their most important particularities in the delimitation of their analysis units. When they are well carried out, these researches constitute an excellent source of updating medical knowledge and a magnificent opportunity for young researchers to train in the scientific research field.